THE ADVERSE EFFECTS OF SMARTPHONES ON COGNITIVE ACTIVITY IN THE EDUCATIONAL PROCESS AND WAYS TO MITIGATE THEM - Qosimova X. T.; Ikramova N. A.; Juraboyeva D. N.; Mukhtorova D. A. (The Conference Hub, 2025)
Modern technologies have deeply penetrated all spheres of human life, including the educational process. Today, smartphones are not only communication tools but also means of obtaining information, studying, and facilitating daily life. However, along with these conveniences, smartphones also have negative effects. In particular, their adverse impact on students' cognitive activity deserves special attention.